Citizenship as a legal institution and category of law theory and state - Turlayev, A.V.; Poleva, I.A.; Tuyakova, N.B. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2022)
The article demonstrates the theoretical and historical problems of defining citizenship as a legal institution and the definition of its main features. The dynamic nature of this political and legal phenomenon, associated in the law theory with the state, is revealed. In a historical retrospective, using the citizenship institution expe-rience for the state-legal regulation purpose relations between the individual and the state is considered. The studies of citizenship in different historical periods, the variability and institution development in the theories and various authors’ approaches are undertaken. The investigation purpose is to identify the main citizenship features by determining the goals and political and legal institution objectives. With the general and special research methods support, the analysis and generalization of historical and theoretical material, political and legal acts that define the concept and signs of citizenship as a legal and theoretical category are carried out. As a result, citizenship is considered as the main and defining republic feature as one of the main state forms. It is a political and legal category requiring legal regulation. The article concludes that citizenship is the main factor in the modern state existence, with a republican government form. The relationship between the indi-vidual and the state, mediated in the citizenship form, needs more detailed legal regulation.
Азаматтық мемлекет және құқық теориясының құқықтық институты және категориясы ретінде
Гражданство как правовой институт и категория теории права и государства
Keywords: citizenship; law theory; constitutional law; state; republic; legal institution; human rights; legal regulation; legal category